Twelve-month findings of the MOVE Frankston randomised controlled trial of interventions to increase recreation facility usage and physical activity among adults. - Ben J Smith (Public Library of Science (PLoS), 2021)
Substantial cross-sectional evidence and limited longitudinal research indicates that the availability of recreational facilities (e.g., parks, fitness centres) is associated with physical activity participation. However, few intervention trials have investigated how recreational infrastructure can be used to reduce inactivity levels in communities. The MOVE Frankston study aimed to assess the impact of low intensity strategies to promote use of a multi-purpose leisure and aquatic centre in a socioeconomically diverse, metropolitan community. This randomised controlled trial of two years' duration compared public awareness raising (control condition) with two interventions: mailed information about the centre and a free entry pass (I-O); and this minimal intervention supplemented by customer relations management support through telephone contact, mailed promotional materials and additional incentives (I+S). Participants (n = 1320) were inactive adults living in the City of Frankston, Melbourne Australia. There were 928 people (70.3%) followed up at 12 months (61.2% female, 52% ≥55 yrs). Compared with controls, attendance at the Centre once or more was higher in both the I-O (OR 1.79, 95% CI 1.28-2.50) and I+S groups (OR 1.46, 95% CI 1.03-2.07). The proportion of people using the centre weekly did not differ by group. The odds of being in contemplation or preparation to use the Centre were higher in both the I-O (OR 1.76, 95% CI 1.28-2.42) and I+S groups (OR 1.48, 95% CI 1.07-2.06). Total physical activity and related social and cognitive factors did not differ between the groups. The findings show that the low intensity promotional strategies prompted occasional attendance and increased readiness to use this recreational facility, a level of behaviour change unlikely to reduce non-communicable disease risk. It is recommended that more frequent customer relations contact, and involvement of healthcare providers, be tested as strategies to encourage inactive adults to take up physical activity opportunities at recreational facilities of this type.